Uncovering Pluralistic Ignorance to Change Men’s Communal Self-descriptions, Attitudes, and Behavioral Intentions - Van Grootel, Sanne; Van Laar, Colette; Meeussen, Loes; Schmader, Toni; Sczesny, Sabine (Frontiers in Psychology, 2018)
Gender norms can lead men to shy away from traditionally female roles and occupations in communal HEED domains (Healthcare, Early Education, Domestic sphere) that do not fit within the social construct of masculinity. But to what extent do men underestimate the degree to which other men are accepting of men in these domains? Building on research related to social norms and pluralistic ignorance, the current work investigated whether men exhibit increased communal orientations when presented with the true norms regarding men’s communal traits and behaviors vs. their perceived faulty norms. Study 1 (N = 64) revealed that young Belgian men indeed perceive their peers to hold more traditional norms regarding communal and agentic traits than their peers actually hold. Study 2 (N = 319) presented young Belgian men with altered norms to manipulate exposure to men’s actual normative beliefs (i.e., what men truly think), their perceived norms (i.e., what men believe other men think), or a no information control. When men were presented with actual rather than perceived norms, they altered their own self-descriptions, future behavioral intentions, and broader gender-related social attitudes in a more communal direction. In particular, men who were presented with information about men’s actual beliefs regarding the compatibility between communal and agentic traits exhibited the strongest movement toward a more communal orientation. The findings show that participants in conditions that uncover pluralistic ignorance adapted their attitudes and behaviors to be more in line with the actual norm: adopting a more communal self-concept, having lower intentions to hide future communal engagement, and supporting more progressive gender-related social change. The results are discussed in terms of influences of norms on men’s communal orientations and broader attitudes toward gender-related social change, and the down-stream implications for increased gender-equality in HEED domains where men remain highly underrepresented.